The evaluation of acoustic characteristic performance on natural sound absorbing materials from cogon grass waste - Ahmad Nordin, Mohd Nor Azmi (2019)
In the past few decades, synthetic fibers are been used widely in the field of sound absorption due to their superior characteristics such as durable and chemical resistant. However, there are several disadvantages of synthetic fibers such as non-biodegradability and hazards to the health of human. In this research, the natural sound absorber from cogon grass was investigated. The objective of the research was to evaluate the performance of cogon grass physical characteristics on its acoustical behavior, to evaluate the effect of sodium hydroxide (NaOH) treatment times on physical and acoustical characteristics of cogon grass, to investigate the decay effects after it was left over for twelve months and lastly to compare and verify the acoustical results with theoretical models based on (Delany-Bazley and Miki Model). The measurement of acoustical characteristics which are sound absorption coefficient (SAC) and noise reduction coefficient (NRC) were done by using impedance tube method (ITM). The samples of cogon grass were tested in a way of the untreated and treated with NaOH in varied soaked hours which are one, two, three, four and five hours. Scanning electron microscope (SEM) and density kit were used to investigate physical characteristics. The research confirmed that physical characteristics of tortuosity and airflow resistivity values tend to increase with the increment of treatment times, but the density and porosity tend to decrease. Untreated samples were tested with varied thicknesses of 10, 20, 30, 40 and 50mm. The results show SAC value increases when the thickness of the sample was increased. Treated samples results show the least treated sample (1 hour) reached the maximum SAC value and indicated the highest value of NRC which is 0.50. The results also show a reduction in sound absorption value after the samples were left for twelve months. Verification parts demonstrated that Delany-Bazley and Miki Model can predict approximately pattern compared with ITM results because of the theoretical models are developed by a simple empirical model approach. Overall, cogon grass samples have the good characteristics to be an acoustic material component.